Study of ferromagnetic particles trajectories pollution in a magnetic cleaners - Пузік, С.О.; Шевчук, В.С.; Манзій, В.С. (Proceedings of National Aviation University (archive), 2006)
The ways precipation of ferromagnetic particles of soiling in the magnetic liquid and gas cleaners were explored. It was determined, that the ways of precipation particles of soiling were discerned such as straight lines.